Functional Enzyme Mimics for Oxidative Halogenation Reactions that Combat Biofilm Formation. Issue 36 (19th June 2018) - Herget, Karoline; Frerichs, Hajo; Pfitzner, Felix; Tahir, Muhammad Nawaz; Tremel, Wolfgang
Abstract: Transition‐metal oxide nanoparticles and molecular coordination compounds are highlighted as functional mimics of halogenating enzymes. These enzymes are involved in halometabolite biosynthesis. Their activity is based upon the formation of hypohalous acids from halides and hydrogen peroxide or oxygen, which form bioactive secondary metabolites of microbial origin with strong antibacterial and antifungal activities in follow‐up reactions. Therefore, enzyme mimics and halogenating enzymes may be valuable tools to combat biofilm formation. Here, halogenating enzyme models are briefly described, enzyme mimics are classified according to their catalytic functions, and current knowledge about the settlement chemistry and adhesion of fouling organisms is summarized. Enzyme mimics with the highest potential are showcased. They may find application in antifouling coatings, indoor and outdoor paints, polymer membranes for water desalination, or in aquacultures, but also on surfaces for food packaging, door handles, hand rails, push buttons, keyboards, and other elements made of plastic where biofilms are present. The use of natural compounds, formed in situ with nontoxic and abundant metal oxide enzyme mimics, represents a novel and efficient "green" strategy to emulate and utilize a natural defense system for preventing bacterial colonization and biofilm growth. Abstract : Many halogenated compounds in nature have strong antibacterial and antifungal activities. The corresponding halogenating enzymes are valuable tools to combat biofilm formation. Halogenating enzymes and enzyme mimics are described, and settlement chemistry and adhesion of fouling organisms are summarized. Enzyme mimics with the highest potential for antifouling coatings in indoor/outdoor paints, aquacultures, polymer coatings, or food packaging are showcased.